2005
DOI: 10.4049/jimmunol.174.1.345
|View full text |Cite
|
Sign up to set email alerts
|

Vα and Vβ Public Repertoires Are Highly Conserved in Terminal Deoxynucleotidyl Transferase-Deficient Mice

Abstract: T cell repertoires observed in response to immunodominant and subdominant peptides include private, i.e., specific for each individual, as well as public, i.e., common to all mice or humans of the same MHC haplotype, Vα-Jα and Vβ-Dβ-Jβ rearrangements. To measure the impact of N-region diversity on public repertoires, we have characterized the αβ TCRs specific for several CD4 or CD8 epitopes of wild-type mice and of mice deficient in the enzyme TdT. We find that V, (D), J usage identified in public repertoires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
3
39
0
Order By: Relevance
“…Unlike the starting αβ T cell repertoire, we found numerous examples of public Vγ2 clonotypes in the starting repertoire nearly all of which expressed the Jγ1.2 segment; selection produced an astonishingly similar repertoire among unrelated individuals. Similar to what has been observed for public αβ T cell repertoire, public Vγ2 clonotypes have minimal CDR3 diversity and are predominantly composed of germline-encoded residues [19]. Historically, the disproportionate engagement of MHC molecules with CDR1/2 of the αβ TCR was proposed to explain the phenomenon of public responses with minimal CDR3 diversity in these cells [19].…”
Section: Discussionmentioning
confidence: 67%
“…Unlike the starting αβ T cell repertoire, we found numerous examples of public Vγ2 clonotypes in the starting repertoire nearly all of which expressed the Jγ1.2 segment; selection produced an astonishingly similar repertoire among unrelated individuals. Similar to what has been observed for public αβ T cell repertoire, public Vγ2 clonotypes have minimal CDR3 diversity and are predominantly composed of germline-encoded residues [19]. Historically, the disproportionate engagement of MHC molecules with CDR1/2 of the αβ TCR was proposed to explain the phenomenon of public responses with minimal CDR3 diversity in these cells [19].…”
Section: Discussionmentioning
confidence: 67%
“…Irrespective of the selection processes that determine the recruitment of individual pMHC epitope-specific clonotypes into the memory T-cell pool, these observations indicate that such shared, or "public," TCRs must first be present in the naïve T-cell repertoire of multiple individuals. Furthermore, it has been suggested that public TCR sequences might be generated more efficiently during the recombination process, thereby explaining differential interindividual frequencies of naïve T-cell clonotypes (5,6).…”
mentioning
confidence: 99%
“…Importantly, relapse in wt animals is not due to epitope spreading but to MOG-specific T lymphocytes expressing new public V␣ and V␤ rearrangements containing N additions. As reported for various ID epitopes (22,23), MOG 35-55-specific public T cell repertoires of TdT ϩ and TdT Ϫ/Ϫ littermattes are closely similar. Wt and TdT Ϫ/Ϫ mice share the public CDR3␤ sequence GETGGNYAEQ (Ref.…”
Section: Discussionmentioning
confidence: 55%
“…Shorter CDR3␤ sequences are also found in LNC and cells infiltrating the CNS of TdT Ϫ/Ϫ mice: GGTGDAEQ (two of five for LNC and two of five for CNS-infiltrating cells), GDAGDAEQ (two of five and one of five) and AGTGDAEQ (two of five and two of five). These shorter CDR3␤ sequences are characteristic of TdT Ϫ/Ϫ rearrangements as reported for naive T lymphocytes (21,30) and T cells specific for various protein epitopes (22,23,31).…”
Section: T Cell Repertoires Against the Id Peptide Of The Murine Mog Inmentioning
confidence: 99%
See 1 more Smart Citation